2015
DOI: 10.1542/peds.2015-0285
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pediatric Asthma Care and Outcomes Across Multiple Hospitals

Abstract: BACKGROUND AND OBJECTIVES: Gaps exist in inpatient asthma care. Our aims were to assess the impact of an evidence-based care process model (EB-CPM) 5 years after implementation at Primary Children's Hospital (PCH), a tertiary care facility, and after its dissemination to 7 community hospitals.METHODS: Participants included asthmatics 2 to 17 years admitted at 8 hospitals between 2003 and 2013. The EB-CPM was implemented at PCH between January 2008 and March 2009, then disseminated to 7 community hospitals betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 39 publications
1
50
1
Order By: Relevance
“…In a report of a care pathway for asthma undertaken at eight hospitals in the pediatric hospital network of Intermountain Healthcare, readmissions and length of stay at the tertiary care hospital decreased with a trend toward significant cost reduction which persisted over a 5-year period. For the community hospitals, however, the readmission rate did not change significantly, but length of stay and cost both decreased though the sample size was small at the community hospitals [13]. In another report from a multicenter study involving 21 hospitals [19], providers used a consensus-derived pathway for inpatients with bronchiolitis and showed reduction in resource utilization from pre-implementation measurements including use of any bronchodilator (29 %), use of any steroid (68 %), chest radiography (44 %), and length of stay (5 h).…”
Section: Standardization In Networkmentioning
confidence: 88%
See 2 more Smart Citations
“…In a report of a care pathway for asthma undertaken at eight hospitals in the pediatric hospital network of Intermountain Healthcare, readmissions and length of stay at the tertiary care hospital decreased with a trend toward significant cost reduction which persisted over a 5-year period. For the community hospitals, however, the readmission rate did not change significantly, but length of stay and cost both decreased though the sample size was small at the community hospitals [13]. In another report from a multicenter study involving 21 hospitals [19], providers used a consensus-derived pathway for inpatients with bronchiolitis and showed reduction in resource utilization from pre-implementation measurements including use of any bronchodilator (29 %), use of any steroid (68 %), chest radiography (44 %), and length of stay (5 h).…”
Section: Standardization In Networkmentioning
confidence: 88%
“…On the other hand, some pediatric hospital systems have committed to broad implementation of care plans in the daily workflow [10][11][12][13]. Many clinical practice guidelines address single disease states or conditions within pediatric networks, single hospitals, or other user groups.…”
Section: Standardizationmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Other reports are limited to children and use only preprogram and postprogram comparisons. 36,[64][65][66][67][68][69][70][71][72][73] Ragazzi et al 36 were able to improve 4 of 8 care processes, but in exit interviews, staff reported those improvements were unlikely to be sustained without ongoing external support. Adding nurse managers, plus "intense interaction" with families and home visits, both Woods et al 72 and Lob et al 69 demonstrated a pre-to-post decrease in rates of asthma ED visits (68% and 70%, respectively), whereas Bunik et al 64 and Vernacchio et al 68 used similar methods but found no improved outcomes, with improvement only in documentation of care processes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Additionally, asthma clinical pathways have been shown to decrease LOS and improve resource utilization. [9][10][11][12][13] Previous inpatient pediatric asthma quality initiatives achieved these outcomes through promotion of systemic corticosteroids, 14 use of spacer with metered-dose inhaler, 15,16 or use of objective measures to determine albuterol weaning readiness.…”
mentioning
confidence: 99%